PENGEMBANGAN MODUL AJAR PEMBELAJARAN DSI BERBASIS PBL MENGGUNAKAN PENDEKATAN DEEP LEARNING PADA MATA PELAJARAN INFORMATIKA KELAS VII SMP - Zubaidah, Siti; Ahmad Smaragdina, Azhar; Cahyaning Pininta Kustia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the limited availability of learning resources in Informatics, which are still predominantly dominated by printed textbooks, thereby reducing students' active engagement in the learning process. This study aimed to develop a Digital Social Impact (DSI) learning module based on Problem-Based Learning (PBL) using a Deep Learning approach for seventh-grade junior high school students.The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through a literature review and questionnaires administered to material experts and media experts. The research instruments used a four-point Likert scale and were analyzed quantitatively using validity percentages.The results showed that the developed learning module achieved a validity percentage of 78.12%, categorized as very valid, in the material expert validation and 90.62%, categorized as very valid, in the media expert validation. These findings indicate that the module has fulfilled the criteria of content feasibility, presentation, language, and graphic design. Therefore, the PBL-based learning module using a Deep Learning approach is considered suitable for use in Informatics learning and has the potential to enhance students’ learning engagement, critical thinking skills, and problem-solving abilities in addressing various issues related to the social impacts of Informatics.